Knowledge, attitude, and practice toward Avian flu among students in a public university in Pahang, Malaysia - Ibrahim, Hanadi; A. Rahman, Nor Azlina; Mamat, Suhana; Haque, Mainul (Wolters Kluwer - Medknow, 2017)
Background: Avian influenza (AI) is a disease that causes infection in birds with AI A virus. In Malaysia, the first outbreak of AI in poultry was detected in Kelantan on August 2004. This study aimed to examine the knowledge, attitude, and practice (KAP) toward AI among students in a public university in Pahang, Malaysia. Materials and Methods: This was a cross‑sectional study had been conducted starting from March 11, 2013 until March 20, 2013 on 100 students. Data regarding sociodemographics characteristics and KAP toward AI had been collected by distributing the questionnaires to the participants in their hostels and classes and were analyzed using SPSS software. Results: The mean knowledge, attitude, and practice were 21.47 (4.181), 44.28 (4.845), and 8.69 (1.921), respectively. There were significant differences regarding the level of knowledge among different group of age (P = 0.041) and departments (P = 0.001). The older group of individuals were more knowledgeable. The students from health science had a higher level of knowledge. Regarding the practices, there was no significant difference in the level of practice toward the prevention of AI across the different gender, age, hometown, and department. There was also the significant correlation between knowledge and practices (r = +0.217, P = 0.030), but no association was found between knowledge and attitude or attitude and practice. Conclusion: Overall participants had moderate knowledge and practices regarding prevention of AI. Nonetheless, they had expressed good positive attitude toward the prevention of disease. Therefore, public health agencies should play a role to spread information and increase awareness among students about this infectious disease.